Legal Protection of Customary Forests, the Sacred Land of the Dayak Customary Law Community in Central Kalimantan in Maintaining Local Wisdom and Anticipating Global Climate Change - Budhi Widodo (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2025)
The study aims to analyzed the national legal framework and relevant international instruments for the protection of sacred customary forests in Indonesia. Following Constitutional Court Decision No. 35/PUU-X/2012, the concept of customary forests has undergone a significant shift from the previous category of “state forests” or forests controlled by the state, to the recognition of the existence and rights of customary law communities over forest areas within their customary territories. However, in fact, the implementation of the recognition and designation of customary forests faces administrative obstacles, overlapping authorities, and internal ministerial regulations that are not yet fully aligned. The study used a normative legal research approach, analyzing regulations, judicial decisions, ministerial technical regulations, various regional legal products, and academic literature to identify legal gaps and formulate policy recommendations. The results show that the nature and function of sacred customary forests are related to customs, culture and belief systems and religious functions of the Dayak customary law community. Various legal political policies have been taken by the regional government to provide legal protection for sacred customary forests such as: the determination of sacred customary forest areas in the RTRWP/K, identification, inventory, and validation of customary law communities and the determination of regional legal products regarding the recognition and protection of Dayak customary law communities. However, harmonization of cross-ministerial regulations is urgently needed to protect the sacred values ​​inherent in customary and sacred forests.